SENSORES ELETROQUÍMICOS BASEADOS EM FILMES LBL DE FTALOCIANINA METALADA E POLÍMERO SILSESQUIOXANO. - Jesus, Cliciane Guadalupe de (2013)
In this thesis, it is described the preparation, characterization and application of LbL films based on the 3- n - propylpyridinium silsesquioxane polymer (SiPy+Cl-) and copper (II) tetrasulfophthalocyanine (CuTsPc), denoted as (SiPy+Cl-/CuTsPc)n, for construction of sensors and biosensors. These films (SiPy+Cl-/CuTsPc)n, were applied as a sensor for promethazine hydrochloride (PMZ) and hydrogen peroxide (H2O2). In addition, taking advantage of the property to the film in electrocatalyzing the reduction of H2O2, an enzymatic amperometric biosensor was constructed by the immobilization of the glucose oxidase enzyme (GOx) on the film for detection of glucose, based on the detection of H2O2 produced in the enzymatic reaction. The UV-Vis spectroscopic technique showed that the adsorption of phthalocyanine occurred linearly indicating that the approximately the same amount of the species is immobilized at each bilayer. The interaction between the sulfonic group and the pyridinium ring is responsible for the support of the films due to the shift of the vibration associated with sulfonic groups. The film (SiPy+Cl-/CuTsPc)5 was highly electrocatalytic and sensitive determination of PMZ. The oxidation process of PMZ molecule presented two peaks at 0.48 and 0.79 V. After optimization of the square wave voltammetry parameters (f = 100 s-1, a = 40 mV and ΔEs = 2 mV), the peak at 0.79 V was used for quantification. Accordingly, the modified electrode obtained a linear response of 3.98 x 10-7 to 3.85 x 10-6 mol L-1 with limits of detection (LOD) and quantification (LOQ) equal to 8.71 x 10-9 mol L-1 (2.79 g L-1) and 9.31 x 10-8 mol L-1 (9.31 g L-1), respectively. The recovery in pharmaceutical samples showed high stability, specificity and accuracy of the method in complex samples without any pre-treatment. The film (SiPy+Cl-/CuTsPc)2 showed excellent electrocatalytic activity for the reduction of H2O2 with a wide linear range (4.97 x 10-6 a 4.76 x 10-5 mol L-1) and low detection limit (0.33 x 10-6 mol L-1). This electrode was modified with the glucose oxidase enzyme (GOx) and coated with Nafion® (Nf) film, which was used to prevent leaching of GOx. The Fourier transform infrared, fluorescence and circular dichroism spectroscopics, showed that the GOx enzyme retains its native secondary structure when immobilized on the LbL film. The resulting biosensor (SiPy+Cl-/CuTsPc)2(SiPy+Cl-/GOx/Nf) exhibited a current response which varied linearly with the concentration of glucose in the range of 1-10 mmol L-1, with LOD = 0.17 mmol L-1, sensitivity of 1.397 μA x 10-7/mmol L-1 and a rapid response time, less than 5 seconds. The Michaelis-Menten constant apparent ( appmK ) was 10 mmol L-1. Furthermore, the biosensor also showed good reproducibility, excellent stability and a long life, without loss of enzymatic activity by a one-week period and remained active for more than three weeks. The use of the polymer Nf decreased the effect of interferents on the response of the biosensor.